Load Flow Analysis and Short Circuit Faults with the Additional Distributed Generation Wind Turbine 300 kW at Andalas University - Fadhel Putra Winarta; Yoli Andi Rozzi (Electrical Engineering Dept, Engineering Faculty, Universitas Andalas, 2021)
The study of electric power flow analysis (Load Flow) is intended to obtain information about the flow of power or voltage in an electric power system network. This information is needed to evaluate the performance of the power system. Electrical power flow problems include calculating the flow and system voltage at certain terminals or buses. The benefits of this power flow study are to find out the voltage at each node in the system, to find out whether all the equipment meets the specified limits to deliver the desired power, and to obtain the original conditions in the new system planning. This study is divided into two: the analysis of data when the conditions have not been added wind turbine and after the addition of 300 kW wind turbine with software power station ETAP software 12.6.0 and the Newton-Raphson method will be used in analyzing the power flow of the electric power system. Based on the results of the tests, it is found that the overall value of losses for power flow before the addition of DG is 0.031 MW and 0.037 Mvar, for the voltage drop with the lowest percentage, namely on bus 10 with a percentage of 96.45 for the 0.4 kV system and the 20 kV system on bus 19 with a percentage of 99.03, the largest% PF load was in lump 1 with 98.64 and the smallest% PF was in lump7 with a value of 84.92. The short circuit data value on the 20 kV bus system at Andalas University before the addition of DG with 3-phase disturbances averaged 13.354 A, 1-phase disturbances averaged 3.521 A, 2-phase disturbances averaged 11.719 A and 2 ground phases of 12.842 A Whereas for the value of power flow after the addition of DG in the form of the wind turbine of 300 kW the overall value of losses is 0.032 MW and 0.042 MvarAR, for the voltage drop with the percentage for voltage drop with the lowest percentage is bus 10 with a percentage of 96.63 for system 0, 4 kV and a 20 kV system on bus 14 with a percentage of 98.1, the largest% PF load is in lump 1 with 98.64 and the smallest% PF is in lump7 with a value of 84.92. The short circuit data value on the 20 kV bus system at Andalas University after the addition of DG with 3 phase disturbances has an average value of 13.354 A, 1 phase disturbance averages 3.523 A, 2 phase disturbances average 11.737 A and 2 phases ground is 12.059 A For the source in this system, after the addition of DG, there was a change in the% PF of the PLN grid, namely 79.53 and the wind turbine -83%.